Knowledge exploration: selected works on Quran ontology development - K., Farooqui Najam; Noordin, Mohamad Fauzan (Little Lion Scientific Islamabad Pakistan, 2015)
This paper presents key features and challenges ahead for the development and knowledge retrieval of Quran ontology. Recent studies have made significant advances towards the development of Quran ontology. In the recent past, there have been numerous studies conducted on the application of semantic technologies on Quran. Contribution of this paper is its focus on finding the direction of knowledge exploration in Quran. Several studies on Quran ontology development help us in analyzing its linguistic features. Another dimension where Quran excels is the Knowledge of it. There are few studies that concentrate on retrieval of knowledge from Quran. In this literature review, we have included studies that can help us in developing semantic application for knowledge exploration from Quran. This paper devises challenges mainly focusing towards exploration of knowledge in the Quran and summaries research in this area, discuss key features and open research issues.